Orthokeratinizing odontogenic keratocyst transformation in to verrucous hyperplasia- A case report of rare entity - Balasubramaniyan Nathiya, MDS; D. Durairaj, MDS; M. James Antony Bhagat, MDS; Ganesan Suresh Kumar, MDS; B. Raj Prakash (Elsevier, 2022)
Verrucous hyperplasia arising from an odontogenic keratocyst is extremely rare. We report an unusual case of orthokeratinizing odontogenic keratocyst that get transformed in to verrucous hyperplasia due to prexisting chronic inflammatory stimuli with absence of HPV, tobacco and candidal infection.